An introduction to the special issue on ‘counterfeiting’ - Antonopoulos, Georgios (Trends in organized crime, 2017)
This paper provides an introduction to the articles and report excerpts included in the special issue of Trends in Organized Crime on ‘Counterfeiting’. The aim of this special issue is to add to the relatively sparse literature currently available that addresses this expansive and complex criminological phenomenon. In particular, the special issue draws together empirical research findings and theoretical accounts on the organization of the counterfeit trade across a broad spectrum of goods, and highlights a number of issues associated with researching counterfeiting.